Dampak Alat Pembelajaran Multimedia dalam Meningkatkan Kemampuan Bahasa Inggris: The Impact of Multimedia Learning Tools in Improving English Language Skills - Rasmita, Rasmita; Pohan, Nurmaliana (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
This study aims to analyze multimedia learning tools' impact on improving grade VI students' English language skills at SDN 02 Lubuk Buaya, Padang City. In today's digital era, technology in education is increasingly important, especially in improving language skills. The method used is a quantitative experiment with a pre-test and post-test approach. The sample consisted of 52 students and was divided into two groups: an experimental group using multimedia applications and a control group using conventional methods. The results showed that multimedia significantly improved students' English skills, especially vocabulary comprehension and speaking skills. Data analysis revealed a significant difference between the control and experimental groups, which showed better progress. These findings confirm the benefits of integrating multimedia technology in language teaching, which can help students be more engaged and motivated in learning English. This study provides empirical evidence regarding the effectiveness of multimedia use in improving students' English learning outcomes. Multimedia tools based on mobile applications and e-learning platforms are becoming more widespread to improve students' English skills. Therefore, it is important for schools and educators further to integrate multimedia technology into the English language learning curriculum. In addition, training for teachers in the use of multimedia tools is also needed to ensure that the technology is used effectively. Thus, students' English learning outcomes can be significantly improved by applying this method.